Caenorhabditis Elegans Mutants Predict Regulation of Fatty Acids and Endocannabinoids by the CYP-35A Gene Family - Aarnio, Vuokko; Lehtonen, Marko; Storvik, Markus; Callaway, James C.; Lakso, Merja; Wong, Garry (Frontiers in Pharmacology, 2011)
Background: Cytochrome P450s (CYPs) are mono-oxygenases that metabolize endogenous compounds, such as fatty acids and lipid signaling molecules, and furthermore have a role in metabolism of xenobiotics. In order to investigate the role of CYP genes in fat metabolism at the molecular level, four C. elegans mutants lacking functional CYP-35A1, CYP-35A2, CYP-35A4 and CYP-35A5 were characterized. Relative amounts of fatty acids, as well as endocannabinoids, which regulate weight gain and accumulation of fats in mammals, were measured while fat contents in worms were visualized using Oil-Red-O staining. Results: The cyp-35A1 and cyp-35A5 mutants had a significantly lower intestinal fat content than wild-type animals, whereas cyp-35A2 and cyp-35A4 mutants appeared normal. The overall fatty acid compositions of CYP mutants did not alter dramatically, although modest but significant changes were observed. cyp-35A1 and cyp-35A5 mutants had significantly higher levels of C18:1n7 and lower C18:2n6c. All four mutants had higher relative amounts of C18:1n7 than the wild-type. In the cyp-35A5 mutant, the levels of the endocannabinoid anandamide were found to be 4.6 fold higher than in wild-type. Several fatty acid synthesis genes were over-expressed in cyp-35A1 including fat-2. Feeding oleic or elaidic triglycerides to wild-type animals demonstrated that cyp-35A1 transcriptional levels are insensitive to environmental exposure of these fats, while cyp-35A2, cyp-35A4, and cyp35A5 were significantly down regulated. Conclusions: These results demonstrate a dynamic role for CYP-35A subfamily members in maintaining the diversity of fatty acid profiles in C. elegans, and more generally highlight the importance of CYPs in generating both structural and signaling fatty acid functions in other organisms.